Resource Identification and Level of Understanding of Particle Dynamics Concepts - Kadir Masalesi, Akbar (International Journal of Education and Teaching Zone, 2022)
The need for a complete understanding of concepts to prevent imperfect understanding still needs to be prioritized. Many student difficulties are still due to misconceptions that have not been straightened out. Resource theory also reveals this, which explains the phenomenon of imperfect student understanding. This study aims to reveal the students' difficulties in understanding physics concepts on the topic of Newton's laws. The study was conducted on 82 students of class X by using 11 questions of choice of reasons, students' answer choices became quantitative, and the reasons for students' answers became sources of qualitative data. Quantitative data were analyzed using descriptive statistics. Meanwhile, the data was analyzed qualitatively using the Miles and Huberman analysis stages to see students' level of understanding and activated resources. The results showed that many students still experienced very low conceptual understanding, averaging 37.58. This is shown in the 11 questions. Only five questions can be answered correctly by more than 50% of students. At the same time, fewer than 30% of students can answer the six questions correctly. However, only 11.53% of students can answer correctly and are accompanied by reasons by scientific concepts. The reasons given in answering indicate the existence of misconceptions experienced by students, with a percentage of 14.52%. At the same time, the remaining 55.54% indicate that students are at the level of not knowing by showing students' answers without giving reasons.